Infant Feeding Regimens and Gastrointestinal Tolerance: A Multicenter, Prospective, Observational Cohort Study in China - Meng Mao MD; Lan Zhang MD; John Ge MD; Jian Yan PhD; Robert Northington PhD; Manjiang Yao MD, PhD; Joyce Nowacki MS, RD; Nicholas P. Hays PhD (SAGE Publishing, 2018)
To study feeding tolerance in infants fed formula with increased sn -2 palmitate and oligofructose ( sn -2+OF) in a real-world setting, healthy Chinese infants were enrolled in this 48-day observational study on their current feeding regimens: exclusively breastfed (BF; n = 147), exclusively sn -2+OF formula-fed (FF; n = 150), or mixed-fed with breast milk and sn -2+OF formula (MF; n = 163). Throughout the study, incidence (90% confidence interval) of hard stools was ≤2.1% (0.0-5.3) in FF and 0.8% (0.0-3.5) in MF, with no hard stools in BF. Incidence of watery stools was ≤5.0% (1.0-9.2) in FF and ≥5.1% (2.4-9.3) in MF and BF. Gastrointestinal tolerance scores, although low in all groups (lower scores indicating better tolerance), were slightly higher ( P ≥ .03) in FF (17.5 ± 4.8) and MF (18.2 ± 5.0) versus BF (16.3 ± 3.2) at mid-study; this difference disappeared at study end. Overall, low incidences of hard and watery stools and good feeding tolerance were observed in infants fed sn -2+OF formula.